Teori Tata Bahasa Generatif Transformatif Chomsky serta Aplikasinya dalam Gramatikal Bahasa Arab - Hum, Balkis Aminallah Nurul MIVTAKH (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This article aims to examine Chomsky's Transformative Generative language theory and its application in Arabic grammar. The method used in this study is qualitative based on literature study, which is a research method that provides an explanation by using analysis based on the literature that supports TGT studies. The research object of this study is Chomsky's language theory, namely Transformative Generative Grammar (TGT). This research answers two questions. First,